Geometric morphometry of the head in sand flies (Diptera: Psychodidae: Phlebotominae), an alternative approach to taxonomy studies - Godoy, Rodrigo Espíndola; Shimabukuro, Paloma Helena Fernandes; Dos Santos, Thiago Vasconcelos; Pessoa, Felipe Arley Costa; Da Cunha, Alda Eunice Farias Lobato; Santos, Fabrício Kássio Moura; Vilela, Maurício Luiz; Rangel, Elizabeth Ferreira; Galati, Eunice Aparecida Bianchi (Zootaxa, 2018)
Almost 30% of female American sand flies are morphologically indistinguishable from one another. These females belong to species-complexes or groups with closely related species, making species-level identification difficult or even impossible. This fact has implications for public health since several of these groups include species which are vectors of human pathogens. Thus, new tools are needed to minimize species-level identification problems. In this context, our research sought to use geometric morphometry in the study of the head of females of closely related species of the genus Psychodopygus, Chagasi series, which includes the following species: P. chagasi, P. complexus, P. squamiventris maripaensis, P. squamiventris squamiventris, and P. wellcomei. We have used ten landmarks distributed on the head of these species. All species were clearly distinguished using the centroid size and shape together. These results highlight the head analysis as an effective tool for future geometric morphometry studies in sand flies.